Marriage in Serbian law and in Comparative perspective - Samardžić, Sandra; Kovaček Stanić, Gordana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
According to the Serbian Family Act marriage is cohabitation between two persons of the opposite sex governed by the law. The same act, prescribes substantial and formal requirements for valid marriage. This paper aims to present a review of these requirements in domestic and comparative law as well. It analyzes each condition separately, giving an overview of their historical development and the way they are regulated today in different legal systems. According to domestic law, substantial requirements are the following: opposite gender, expression of will to get married, cohabitation and lack of marriage impediments. However, there is a tendency in the contemporary family law to reduce marriage impediments, which leads to the liberalization and facilitation of marriage formation. Since marriage is very often concluded in religious form, article also gives an overview of the ecclesiastical rules concerning marriage. Finally, it analyzes and compares statistical data concerning number of concluded marriages and divorces in Serbia thirty years ago and in present time.